2013
DOI: 10.1097/mpg.0b013e318292fa2e
|View full text |Cite
|
Sign up to set email alerts
|

Magnet‐Related Injury Rates in Children

Abstract: The number of ED visits for magnet-related injuries in children may be rising and are underreported, with an increase in the proportion of multiple magnets involvement. In our case series, mandatory standard for toys had no mitigating effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
1
33
0
4
Order By: Relevance
“…Moreover, the batteries from two of the paediatric patients could not be successfully extracted because of the delay in presenting to the hospital, which allowed the batteries to adhere to the oesophagus and stomach. In line with our data, several studies have demonstrated increased rates of battery ingestion by young children due to the development and availability of small, high‐powered batteries in toys and many home appliances …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the batteries from two of the paediatric patients could not be successfully extracted because of the delay in presenting to the hospital, which allowed the batteries to adhere to the oesophagus and stomach. In line with our data, several studies have demonstrated increased rates of battery ingestion by young children due to the development and availability of small, high‐powered batteries in toys and many home appliances …”
Section: Discussionsupporting
confidence: 91%
“…Il ne s'agit donc pas d'une situation exceptionnelle. Dans d'autres pays, la fréquence est également élevée ; plusieurs séries monocentriques ont été publiées ces dernières années : 38 cas en 6 ans, 56 cas en 10 ans, 94 cas en 10 ans, 96 cas en 17 ans dans différents hôpitaux nord-américains [8][9][10][11][12][13]. De plus larges séries ont rapporté 128 cas dans 18 pays jusqu'en 2010, 98 cas dans 17 pays et 149 cas dans 22 pays en 23 ans [11,14].…”
Section: Discussionunclassified
“…Même si la majorité (67 %) des enfants ayant ingéré des aimants avait entre 3 et 10 ans, cette étude montre qu'un tiers était âgé de moins de 3 ans et 12 % étaient atteints de troubles du comportement ou du développement. Dans beaucoup d'études, ce sont les enfants de plus de 3 ans, le plus souvent des garçons (58 à 73 %) qui ont ingéré des aimants [8,[10][11][12][13][14][15][16][17][18][19][20]. De plus, ces ingestions sont plus fréquentes chez ceux atteints de troubles neuro-développementaux (environ 10 %).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is essential to include in the differential diagnosis of acute abdominal pain the ingestion of foreign bodies in pediatric patients due to the increased incidence of these cases which, if not treated on time, can produce death 16 .…”
Section: Discussionmentioning
confidence: 99%